Wirtualna rzeczywistość a sprawa realizmu - Nagłowski, Jacek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The takes issue the VR experience in the context of the concepts of realism. He presents the process of create the cinematic VR and its references to reality in the type of non-fiction media. He also points to the ethical dimension of the issue by referring to Emmanuel Lévinas’ philosophy.